Comparison of combined intra-articular and sub-acromial injection with intra-articular injection in adhesive capsulitis - Manandhar, Rajeev Raj; Khanal, Krishna Raj; Khanal, Himal; Gautam, Saroj (Journal of Kathmandu Medical College, 2021)
Background: The pain and limitation of shoulder function can disrupt daily activities of patients for months to years. Adhesive capsulitis is considered a self-limiting disease but the duration remains uncertain. The brunt of the disease is focussed on the inflamed joint capsule. On this basis, use of corticosteroid injection is justified. However, injection method is not conclusive. Objectives: To compare clinical benefits of intra-articular injection alone versus combined intra-articular and subacromial injections in management of adhesive capsulitis. Methods: Fifty-nine patients with diagnostic criteria for adhesive capsulitis were included in the study from March 2019 to September 2020. Patients were divided into two groups; patients who underwent intra-articular (IA) injection alone (Group 1) and those who received both intra-articular and sub-acromial (IA+SA) injection (Group 2). The injections were landmark guided. Patients were followed up at three, six, and 12 weeks. Pain was recorded using visual analogue scale (VAS) and subjective function using Constant-Murley score. Results: Twenty-eight patients were included in Group 1 (IA) and 31 in Group 2 (IA+SA). Thirty-six patients were female (18 each in Group 1 and Group 2) and 23 patients were male (Group 1 = 13; Group 2 = 10). In the twelfth week, VAS score was reduced in both the groups. On comparing the mean value of Constant-Murley score between the two groups there is significant difference in value recorded at the sixth and twelfth week. Conclusion: The IA+SA injection provides significant reduction in pain and better function in the short term over the IA injection.